A SECONDARY USE FOR THE UNIFORM ACHIEVEMENT TESTS. - Schmidt, Leo A. (The Accounting Review, 1949)
The primary case for the uniform achievement tests of the American Institute's Committee on Selection of Personnel has been argued in these columns. A secondary use to which they may be put has been developed at the University of Michigan and may well find useful adoption elsewhere. One of the most difficult judgments which a college admissions officer, or department head, is called upon to make is the evaluation of credits brought in by students transferring after one or more years at some other college. There is always a human desire to be as generous as possible, for the sake of the transferee as well as for reasons of inter school policy. This desire must be balanced by the need to protect the school's own. reputation when it is staked upon the eventual graduate. The fundamental welfare of the transferee himself as well as the welfare of the advanced. classes into which he will go also demands the accurate appraisal of his achievement to date. The problem is especially pressing in subjects such as accounting where each course in the "accounting major" sequence so directly relies upon the mastery of the accounting courses which have preceded it.